1988
DOI: 10.1016/0014-5793(88)80766-x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human interleukin‐6 (IL‐6/BSF‐2/HSF) regulates the synthesis of acute phase proteins in human hepatocytes

Abstract: Recombinant human IL-6 (rhIL-6) is a potent inducer of the synthesis of acute phase proteins in adult human hepatocytes. A wide spectrum of acute phase proteins is regulated by this mediator. After labeling of rhIL-6 stimulated human hepatocytes with P"S]methionine acute phase protein synthesis was measured by immunoprecipitation. Serum amyloid A, C-reactive protein, haptoglobin, ai-antichymotrypsin and fibrinogen were strongly induced (26-, 23-, 8.6-, 4.6 and 3%fold increases, respectively). Moderate increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
154
3
5

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(172 citation statements)
references
References 18 publications
10
154
3
5
Order By: Relevance
“…25 Dysregulated overproduction of interleukin-6 is found in autoimmune diseases, such as rheumatoid arthritis, multicentric Castleman's disease, and Crohn's disease. [16][17][18]26,27 C-reactive protein is a pentamer of 23-kd subunits that is synthesized and secreted by hepatocytes upon stimulation by a variety of inflammatory cytokines, including tumor necrosis factor-a, interleukin-1, and especially interleukin-6. Therefore, interleukin-6 is closely related to the production of C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Dysregulated overproduction of interleukin-6 is found in autoimmune diseases, such as rheumatoid arthritis, multicentric Castleman's disease, and Crohn's disease. [16][17][18]26,27 C-reactive protein is a pentamer of 23-kd subunits that is synthesized and secreted by hepatocytes upon stimulation by a variety of inflammatory cytokines, including tumor necrosis factor-a, interleukin-1, and especially interleukin-6. Therefore, interleukin-6 is closely related to the production of C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interleukin-6 is closely related to the production of C-reactive protein. [25][26][27][28][29] Accordingly, interleukin-6 and C-reactive protein may become considerably important as differential diagnostic markers between systemic IgG4-related lymphadenopathy and multicentric Castleman's disease. Masaki et al 6 have reported that IgG4-related disease is not associated with an elevated serum interleukin-6 level, and cited measurement of serum interleukin-6 as an important tool of differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, their production of CRP and SAA can be induced only by the combination of IL-1 and IL-6 (9,lO). In contrast, in primary cultures of human hepatocytes, IL-6 alone stimulates the synthesis of the full spectrum of APP that is found in inflammatory states, including CRP and SAA (11,12). These findings suggest that IL-6 is the principal regulator of human APP synthesis.…”
mentioning
confidence: 84%
“…The evidence that in tuberculosis these effects are mediated by cytokines such as IL-1 and TNF has been discussed elsewhere [22], Similarly a raised GO percentage is associated with an acute phase response, perhaps also mediated by IL-1, TNF, and other unidentified cytokines, either directly, or via release of IL-6 [7,13], Moreover, stimulation of synthesis of acute phase proteins by cytokines leads to changes in their glycosylation [13], The association between a raised GO percentage and probable cytokine release is at present entirely circumstantial. If real, it suggests two hypotheses.…”
Section: The Regulation Of Agalactosyl Igg (Go) In Vivomentioning
confidence: 99%